Un casque romain à Sainte-Colombe (Rhône) - Daniel Frascone (Gallia)
A Niederbieber type helmet has been found in a Gallo-Roman gutter while making soundings in the vicinity of Vienne. Incomplete, but in a very good state of preservation, this object is an unusual find.